SCIDOT-17. UNDERSTANDING THE EFFECTS OF MOLECULAR SIZE ON VOLUME OF DISTRIBUTION IN CONVECTION-ENHANCED DELIVERY. (11th November 2019) - Rechberger, Julian S; Power, Erica A; Zhang, Liang; Olson, Ian; Lu, Victor M; Daniels, David J
Abstract: Diffuse midline gliomas harboring the H3K27M mutation, previously known as diffuse intrinsic pontine gliomas (DIPG), are rare and aggressive pediatric brain tumors without cure. One of the major challenge sin DIPG treatment is the effective delivery of therapeutic agents across the blood-brain barrier (BBB) to the tumor and surrounding infiltrating cells. Therefore, strategies that enhance drug delivery to the brain are of great interest. Convection-enhanced delivery (CED) is a technique that bypasses the BBB and increases drug distribution by applying hydraulic pressure to deliver compounds directly and evenly into a target region. However, knowledge in CED pharmacology and convective kinetics is still lacking. In an effort to characterize the feasibility, safety, and distribution in the brain based on molecular size of the delivered agent, we performed infusions of FITC-dextran (range 3, 000 Da–150, 000 Da) comparing CED and osmotic pump-based delivery into the brainstem of rodents. We calculated the area and volume of distribution (Vd ) of the FITC-dextran throughout the brain. Our data showed that the Vd decreased exponentially with increased molecular weight of the FITC-dextran. Interestingly, the Vd can maintain linearity at lower molecular weights. Maximal cross-sectional area and craniocaudal extension of fluorescence also decreased when lowering the infusate size. In addition, we developed a patient-derived DIPG orthotopic xenograft model and performed an image-guided CED cannula installation in the tumor bed. Using 3D bioluminescence imaging and computed tomography, we determined the tumor volume and the positioning of the cannula in the bulk tumor. The summation of these results supports CED as a promising technique for treating DIPG tumors. A better understanding of how drugs distribute by convection will allow us to optimize treatment regimens and, ultimately, offers hope to patients and families with this devastating disease.